Level of physical activity and obesity among the adolescent school children in Bhaktapur: A cross-sectional pilot study - Sainju, Nayan Kamal; Manandhar, Naresh; Vaidya, Anira; Joshi, Sunil Kumar (Journal of Kathmandu Medical College, 2017)
Background: Physical activity is crucial for overall health and well-being of an individual. As childhood obesity has emerged as a serious public health concern, physical activity is a proven tool for prevention and treatment of this type of obesity. As lifestyle and behavior pattern is formed at the adolescence age, it is essential that healthy lifestyle and good food habit should start at this age. Hence, we aimed to fi nd the level of physical activity and obesity among the adolescent school children in this study. Objectives: The objective of the study was to fi nd the level of physical activity and obesity among the adolescent school children in a Bhaktapur school. Method: This is a cross sectional pilot study conducted in October 2015 at a private school in Bhaktapur, Nepal. A total of 83 students studying in class eight, nine and ten were included in the study. A validated self-administered questionnaire was used, height and weight were measured and a BMI index for age percentile growth chart was used to interpret the Basal Metabolic Index of the participants. Result: Out of the total 83 respondents, 31.3% of the respondents performed physical activity for at least 60 minutes a day for more than three days per week and 37.3% participants performed the same for less than three days per week. Twelve percent of the total participants were either overweight or obese. Conclusion: The amount of physical activity in majority of the students is not adequate. Prevalence of overweight and obesity in adolescence is high. Sedentary life style, increasing trends of indoor game and consumption of junk food are responsible for increased prevalence of overweight and obesity in the adolescence. Journal of Kathmandu Medical College Vol. 5, No. 2, Issue 16, Apr.-Jun., 2016, page: 65-70